Enzymatic directed interesterification of palm oil for production of highly unsaturated palm fraction - Habi Mat Dian, Noor Lida (2017)
Palm oil (PO) is a balanced oil with equal parts of unsaturated fatty acids (USAFA) mainly oleic acid (monounsaturated fatty acid, MUFA) and saturated fatty acids (SAFA) mainly palmitic acid. USAFA which include polyunsaturated fatty acids and MUFA are classified as good fat that can reduce the risk of coronary heart disease. The ultimate objective of this study was to produce a highly unsaturated palm fraction by enzymatic directed interesterification (EDIE) of PO and fractionation of the interesterified PO (EDIE PO). EDIE is a process whereby randomization of fatty acids on the triacylglycerol (TAG) molecules of oil takes place at a temperature lower than the melting temperature of its highest melting TAGs, normally the trisaturated (S3) TAGs. The EDIE of oil will eventually result in a structured fat with a high concentration of triunsaturated (U3) and S3 TAGs. Since the S3 TAGs were formed simultaneously with the U3 TAGs, the second objective of this project was to obtain a highly saturated palm fraction. The first part of the study focused on the optimization of the EDIE processing parameters namely enzyme load, reaction temperature and reaction time using Response Surface Methodology in order to obtain EDIE PO having the highest U3 TAGs concentration, with a tolerable if not the lowest amount of by-products (free FAs, monoacylglycerol, and diacylglycerol). The optimum reaction parameters were: enzyme load of 10%, reaction temperature of 30 °C and reaction time of 18 hours. EDIE of PO was able to significantly (p<0.05) increase the percentage of U3 TAG in PO, i.e., from 4.3% before EDIE to 27.6% after EDIE, and S3 TAGs, i.e., from 5.2% before EDIE to 31.9% after EDIE. Differential Scanning Calorimetry melting profile showed that the EDIE PO had two well-separated high-melting and low-melting endothermic peaks, indicating ease of fractionation. The EDIE PO was subsequently subjected to fractionation at 5, 10, 15, 20 and 25 °C to obtain the highly unsaturated palm fraction (palm olein, EDIE POo) and its co-product, a highly saturated palm fraction (palm stearin, EDIE POs). The U3 TAGs and USAFA content of the EDIE POo, and S3 TAGs and SAFA content of the EDIE POs fractions varied depending on the fractionation temperatures. The lower the fractionation temperature, the higher the U3 TAGs and consequently the higher the USAFA content of the EDIE POo. Reducing the fractionation temperature from 25 °C to 5 °C resulted in the increase of the U3 TAGs and USAFA content of the EDIE POo from 34.6% to 43.0% and 66.7% to 75.0%, respectively. The S3 TAGs and SAFA content of the EDIE POs were increased from 50.1% to 92.2% and 82.8% to 97.8%, respectively, when fractionation temperature increase from 5 °C to 25 °C. In conclusion, EDIE of PO followed by fractionation of the EDIE PO were able to produce a highly unsaturated fraction, EDIE POo and yielded a highly saturated fraction, EDIE POs. The highly unsaturated EDIE POo could be used as a healthy cooking oil. The highly saturated EDIE POs could be used as a trans fats alternative.